Identification and pathogenicity of bacteria in Banggai Cardinalfish (Pterapogon kauderni) - Samsu Adi Rahman; Sri Sukari Agustina; Nurul Izza Dg. Pageso (Acta Aquatica: Aquatic Sciences Journal, 2025)
The banggai cardinalfish (Pterapogon kauderni) is an endemic fish species in the Banggai waters of Central Sulawesi, with an attractive body shape, making it a prime target for ornamental fish hobbyists. One of the causes of the decline in the Banggai cardinalfish population is disease infection. This study aims to identify pathogenic bacteria that infect the Banggai cardinalfish and to determine their pathogenicity levels. The research was conducted in two stages: first, isolation and identification of bacteria from the Banggai cardinalfish, and second, pathogenicity tests of the identified bacteria. Four bacterial isolates were obtained from the Banggai cardinalfish, and based on morphological characteristics and biochemical tests, four bacterial types were identified according to Bergey’s Manual of Determinative Bacteriology, namely Microbacterium spp., Rhodococcus spp., Bacillus sp., and Edwardsiella spp. The bacterium with the highest pathogenicity toward the Banggai cardinalfish was Bacillus sp., followed by Edwardsiella spp., Microbacterium spp., and Rhodococcus spp. Based on these results, it can be concluded that the identified bacteria are capable of killing the Banggai cardinalfish. Keywords: Bacterial; Banggai Cardinalfish; Identification; Isolates; Pathogenicity